TYPES OF WRITTEN WORK IN PRIMARY CLASSES AND METHODS OF THEIR ORGANIZATION (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Written work is the highest form of creative work and occupies a special place in school. All speech exercises are subject to the types of written work in a certain content: dictation, presentation and essay. The type of written work should be selected in accordance with the spelling rules gradually mastered by the student, be aimed at consolidating the knowledge, skills and competencies acquired by the student on the topics covered, and be aimed at determining the extent to which the student can apply the knowledge he has learned. The type of written work should be selected in accordance with the spelling rules gradually mastered by the student, be aimed at consolidating the knowledge, skills and competencies acquired by the student on the topics covered, and be aimed at determining the extent to which the student can apply the knowledge he has learned.  Based on the calendar-theme work plan, written work can be carried out on time, but the main issue is to develop activities based on the results.